SPE Western Regional Meeting 2005
DOI: 10.2118/93879-ms
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Waterflood Operations: Hall's Method Revisited

Abstract: Hall's method is a tool for evaluation of an injecting well performance.It is based on the assumption of radial steady-state flow.Besides time series of historical injection pressures and rates, rigorous implementation of Hall's method requires information about the ambient reservoir pressure.In addition, it is assumed that the influence domain radius is constant during the observation period.Neither of these parameters can be measured directly. This paper discusses a new method called slope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…18 then p w /Q is a linear function of 1/Q, and the slope of the plot of this function is the reservoir pressure at the perimeter of the injection zone, see Fig. 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 then p w /Q is a linear function of 1/Q, and the slope of the plot of this function is the reservoir pressure at the perimeter of the injection zone, see Fig. 18.…”
Section: Discussionmentioning
confidence: 99%
“…Silin et al 18 reviewed some uncertainties associated with this method and proposed to partially resolve them using a novel "slope analysis." The idea of using Hall's method in automatic maintenance of a desired target injection rate is similar to that of using a thermostat for maintaining a constant temperature.…”
Section: Dynamic Adaptive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…These pressure data combined with the Hall plot 15 gives the single most important information in the evaluation of the success or failure of the fracture waterflood program. These pressure data combined with the Hall plot 15 gives the single most important information in the evaluation of the success or failure of the fracture waterflood program.…”
Section: Well Monitoring and Reservoir Surveillance Strategymentioning
confidence: 99%
“…Some of the notable contributors include Buell et al (1990), who suggested the use of both bottomhole injection pressure and reservoir pressure instead of the wellhead pressure alone, as used in the conventional Hall plot. Evaluation of the reservoir pressure from a slope-analysis method was offered by Silin et al (2005aSilin et al ( , 2005b. Ideally, the Hall method is suitable for either early injection period or during the post-breakthrough period, because the notion of single-reservoir pressure is entertained.…”
Section: Introductionmentioning
confidence: 99%